Resignificar el bosque: forestería comunitaria y resiliencia en el Guaviare (2021)
After the Peace Agreement between the Colombian government and the FARC guerrillas in 2016, social and ecosystem transformations have occurred. On the one hand, the end of war represents an extensive opportunity for social and environmental development; an inclusive economy and an egalitarian society. On the other hand, since the signing of the agreement, acts of land grabbing, violence and deforestation, have increased. The scope of this study was focused of finding out how community forestry affects the socio-ecosystemic resilience in El Capricho, Guaviare, a province with ecosystem relevance due to the convergence of the tropical savannas of the Orinoquia region with the tropical forests of the Amazon that occurs there; both vital corridors for the water cycle and the moorland ecosystem health, with a population determined to overcome stigmatization, war, and State neglect. The research used a qualitative methodology with an ethnographic case of study; the audiovisual was used as a complementary method. The results are overwhelming; community forestry strengthens socio-ecosystemic resilience, however, this is not enough. Structural changes are necessary to avoid returning to an initial state of violence and marginalization.